2011
DOI: 10.1016/j.neuron.2011.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Spatial Reach of the LFP

Abstract: The local field potential (LFP) reflects activity of many neurons in the vicinity of the recording electrode and is therefore useful for studying local network dynamics. Much of the nature of the LFP is, however, still unknown. There are, for instance, contradicting reports on the spatial extent of the region generating the LFP. Here, we use a detailed biophysical modeling approach to investigate the size of the contributing region by simulating the LFP from a large number of neurons around the electrode. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
524
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(556 citation statements)
references
References 52 publications
(80 reference statements)
30
524
2
Order By: Relevance
“…As shown in other studies, synchronization across such large areas of cortex is unlikely to be orchestrated by multiple LFP sources generated by uncorrelated synaptic activity or local field effects. 34 In support of this, we have shown that pathologic HFO networks have similar breakdown patterns across multiple seizure types (complex partial, generalized tonic-clonic, and secondarily generalized tonic-clonic) and therefore, likely manifest a common underlying epileptogenic process. This nonsynaptic mechanism is distinctly different from other well-described modes of generation of oscillatory activity, where intrinsic oscillatory dynamics of individual neurons coupled by gap junctions organize coherent oscillations, such as gamma oscillations.…”
Section: Discussionsupporting
confidence: 68%
“…As shown in other studies, synchronization across such large areas of cortex is unlikely to be orchestrated by multiple LFP sources generated by uncorrelated synaptic activity or local field effects. 34 In support of this, we have shown that pathologic HFO networks have similar breakdown patterns across multiple seizure types (complex partial, generalized tonic-clonic, and secondarily generalized tonic-clonic) and therefore, likely manifest a common underlying epileptogenic process. This nonsynaptic mechanism is distinctly different from other well-described modes of generation of oscillatory activity, where intrinsic oscillatory dynamics of individual neurons coupled by gap junctions organize coherent oscillations, such as gamma oscillations.…”
Section: Discussionsupporting
confidence: 68%
“…In recent experimental and modeling studies, there has been a lot of debate on the source and spatial extent of LFPs (1)(2)(3)(4)(5)(6)(7)(8)(9). However, most of these studies have used neurons with passive dendrites in their models and/or have largely focused on the contribution of spike-generating conductances to LFPs (7,8,10,11).…”
mentioning
confidence: 99%
“…For correlated activity it is more difficult, but they concluded that "...the LFP recorded by an electrode is dominated by populations with substantial synaptic processes in the recording layer." [27]. Hence, nearby sources contribute most to the LFP and distant sources contributions are subject to strong attenuation.…”
Section: Origin Of Invasive Bci Signalsmentioning
confidence: 99%